How well can you tell? Success of human categorisation of horse behavioural responses depicted in media - Katrina Merkies; Katelyn Trudel (Animal Welfare)
Horses employ a range of subtle to overt behaviours to communicate their current affective state. Humans who are more cognisant of their own bodily sensations may be more attuned to recognising affective states in horses (Equus caballus) thereby promoting positive human-horse interactions. This study investigated human ability to categorise human-horse interactions depicted in media relative to equine behaviour experts and compared participant scores to their level of interoception. Using an online survey, participants (n = 534) categorised 31 photographs and videos as (overt) positive, likely (subtle) positive, neutral, likely (subtle) negative or (overt) negative human-horse interactions from the horse’s point of view and completed the Multidimensional Assessment of Interoceptive Awareness questionnaire (MAIA-2) to assess their level of interoception. Demographic information was also collected (age, gender, education, level of experience with horses, location). Participants differed from expert categorisations of horse affective states across all categories, exactly matching experts only 52.5% of the time and approximately matching experts for positive and negative valence 78.5% of the time. The MAIA-2 did not predict participant ability to accurately categorise human-horse interactions. Women outperformed men in categorising overt positive, overt negative and subtle negative human-horse interactions. Increased levels of education and greater experience with horses were associated with improved categorisation of certain human-horse interactions. More training or awareness is needed to recognise behavioural indicators of horse affect to guide appropriate human-horse activities that impact horse welfare.